2022
DOI: 10.1007/s10006-022-01094-7
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of fibrin-rich platelets and leukocytes (L-PRF) in tissue repair in surgical oral procedures in patients using zoledronic acid—case–control study

Abstract: Introduction Medication-related osteonecrosis of the jaws (MRONJ) is a complication that develops in patients who use or have used antiresorptive or antiangiogenic medications for the treatment of bone metabolic disease and bone metastases. Clinically, MRONJ is characterized by the appearance of an inflammation in soft tissues and exposure of necrotic bone tissue in mandible or maxilla, for a period of 8 weeks, in patients with no history of head and neck radiotherapy that were being or are being treated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 30 publications
0
17
1
Order By: Relevance
“…The studies included belonged to three different categories: controlled intervention studies [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ], before–after (Pre–Post) studies with no control group [ 41 , 42 ], and observational cohort studies [ 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The studies included belonged to three different categories: controlled intervention studies [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ], before–after (Pre–Post) studies with no control group [ 41 , 42 ], and observational cohort studies [ 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…Patients with a high chance of developing MRONJ disease, who had a history of BPs and poor oral hygiene, treated with adjunctive therapy with L-PRF for tooth extraction showed no onset of MRONJ disease. Thus, it could be useful to decrease the rate of MRONJ in both oncologic and non-oncologic patients who need to undergo surgical procedures [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of them is a randomized clinical trial by Palma et al 12 , in which platelet concentrates did not offer additional benefits compared to the benefits achieved only with the surgical and drug protocol used in extractions in patients with post-irradiated head and neck cancer to prevent osteoradionecrosis. In the other five studies 13 , 14 , 15 , 16 , 17 , the results showed a positive effect in the use of platelet concentrate as an adjuvant to other procedures for patients who required antiresorptive therapy and had complications of osteonecrosis of the jaws. However, at least one of the studies showed the need for more clinical trials would bring significant results 17 .…”
Section: Resultsmentioning
confidence: 92%
“…Box 2 presents the analyzed outcomes and the results of the included studies. Six studies evaluated the prevention or treatment of drug-related osteoradionecrosis and osteonecrosis of the jaw using L-PRF as a platelet concentrate 12 , 13 , 14 , 15 , 16 , 17 . One of them is a randomized clinical trial by Palma et al 12 , in which platelet concentrates did not offer additional benefits compared to the benefits achieved only with the surgical and drug protocol used in extractions in patients with post-irradiated head and neck cancer to prevent osteoradionecrosis.…”
Section: Resultsmentioning
confidence: 99%